A New Hydrophilic Binder Enabling Strongly Anchoring Polysulfides for High‐Performance Sulfur Electrodes in Lithium‐Sulfur Battery - Chen, Wei; Lei, Tianyu; Qian, Tao; Lv, Weiqiang; He, Weidong; Wu, Chunyang; Liu, Xuejun; Liu, Jie; Chen, Bo; Yan, Chenglin; Xiong, Jie (Advanced energy materials, 2018)
As one of the important ingredients in lithium‐sulfur battery, the binders greatly impact the battery performance. However, conventional binders have intrinsic drawbacks such as poor capability of absorbing hydrophilic lithium polysulfides, resulting in severe capacity decay. This study reports a new type of binder by polymerization of hydrophilic poly(ethylene glycol) diglycidyl ether with polyethylenimine, which enables strongly anchoring polysulfides for high‐performance lithium sulfur batteries, demonstrating remarkable improvement in both mechanical performance for standing up to 100 g weight and an excellent capacity retention of 72% over 400 cycles at 1.5 C. Importantly, in situ micro‐Raman investigation verifies the effectively reduced polysulfides shuttling from sulfur cathode to lithium anode, which shows the greatly suppressed shuttle effect by the polar‐functional binder. X‐ray photoelectron spectroscopy analysis into the discharge intermediates upon battery cycling reveals that the hydrophilic binder endows the sulfur electrodes with multidimensional Li‐O, Li‐N, and S‐O interactions with sulfur species to effectively mitigate lithium polysulfide dissolution, which is theoretically confirmed by density‐functional theory calculations. A hydrophilic binder with strong polarity and viscosity for anchoring polysulfides is proposed. The novel binder has abundant LiN, LiO, and SO bonds for significant improvements in both cycle retention and rate performance when compared with conventional poly(vinylidene fluoride) (PVDF) binder. In situ micro‐Raman investigation further verifies effectively reduced polysulfides shuttling from the sulfur cathode to the lithium anode by the hydrophilic binder.